Role of toll-like receptors in inflammatory bowel disease. (March 2018) - Kordjazy, Nastaran; Haj-Mirzaian, Arvin; Haj-Mirzaian, Arya; Rohani, Mohammad Mojtaba; Gelfand, Erwin W.; Rezaei, Nima; Abdolghaffari, Amir Hossein
Graphical abstract: Abstract: Inflammatory bowel disease (IBD) is the chronic inflammation of the gastrointestinal tract. Recently, studies of the interplay between the adaptive and innate immune responses have provided a better understanding of the immunopathogenesis of inflammatory disorders such as IBD, as well as identification of novel targets for more potent interventions. Toll-like receptors (TLRs) are a class of proteins that play a significant role in the innate immune system and are involved in inflammatory processes. Activation of TLR signal transduction pathways lead to the induction of numerous genes that function in host defense, including those for inflammatory cytokines, chemokines, and antigen presenting molecules. It was proposed that TLR mutations and dysregulation are major contributing factors to the predisposition and susceptibility to IBD. Thus, modulating TLRs represent an innovative immunotherapeutic approach in IBD therapy. This article outlines the role of TLRs in IBD, focusing on both animal and human studies; the role of TLR-targeted agonists or antagonists as potential therapeutic agents in the different stages of the disease is discussed.